Agresiones fisicas y verbales a médicos de hospitales del Seguro Social de Salud en Chiclayo - Morales-Castro, Luisa Jackelini (2018)
ABSTRACT Objective: to estimate the frequency and characteristics of physical and verbal aggressions to doctors of the health insurance hospitals. Material and Methods: descriptive study, 112 physicians were surveyed using the questionnaire of the International Labor Organization adapted to the objectives of the research and the characteristics of the most important incident and the perception of the triggering factors were evaluated. Results: 87.5% were male and 40% corresponded to clinical specialties. 79.46% suffered violence at some time in their professional life and 66.06% in the last year. 98.64% were verbal aggressions. The main aggressor was the relative of the patient (62.92%). 19.10% suffered some type of physical or psychological harm. Of those who did not report (82.02%), 25.8% considered the registry to be of little use. Conclusion: violence against physicians is frequent in hospitals of the social health insurance and it is not notified, it needs to be treated comprehensively and prevented.